The School as a Socialization Context: Understanding the Influence of School Bonding and an Authoritative School Climate on Class Skipping. Issue 8 (November 2019) - Keppens, Gil; Spruyt, Bram
This study contributes to the literature on school-based strategies to prevent and reduce truancy by investigating the relationship between an authoritative school climate and class skipping. We use data from The Programme for International Student Assessment with 15-year-old pupils ( N = 2, 539) in secondary education in Flanders, the Dutch-speaking part of Belgium, to answer three research questions: (a) Is there a relationship between an authoritative school climate and class skipping? (b) Is this relationship mediated by individual school bonding? (c) Does school bonding moderate the relationship between an authoritative school climate and class skipping? In line with the authoritative school climate model, our results indicate that class skipping occurs less frequently in authoritative schools, irrespective of a pupil's personal background or the school composition. In addition, this study demonstrates that (a) the influence of authoritative socialization at least partly acts through the enhancement of school bonding and (b) the link between school bonding and class skipping is stronger in authoritative schools. In the discussion, we elaborate on the implications of our findings.